Equity-oriented toolkit for health technology assessment and knowledge translation: application to scaling up of training and education for health workers - Walker Peter; Hatcher Roberts Janet; Tugwell Peter; Ueffing Erin; Hamel Nadia; Welch Vivian (Human Resources for Health, 2009)
Abstract Human resources for health are in crisis worldwide, especially in economically disadvantaged areas and areas with high rates of HIV/AIDS in both health workers and patients. International organizations such as the Global Health Workforce Alliance have been established to address this crisis. A technical working group within the Global Health Workforce Alliance developed recommendations for scaling up education and training of health workers. The paper will illustrate how decision-makers can use evidence and tools from an equity-oriented toolkit to scale up training and education of health workers, following five recommendations of the technical working group. The Equity-Oriented Toolkit, developed by the World Health Organization Collaborating Centre for Knowledge Translation and Health Technology Assessment in Health Equity, has four major steps: (1) burden of illness; (2) community effectiveness; (3) economic evaluation; and (4) knowledge translation/implementation. Relevant tools from each of these steps will be matched with the appropriate recommendation from the technical working group.